Brand Whitlock papers - Whitlock, Brand, 1869-1934.
Correspondence; diaries; journals; speeches; addresses; manuscripts of novels, short stories, and other works; literary notes; reviews; biographical material; financial records; scrapbooks; clippings; printed matter; memorabilia; photographs; and other papers relating chiefly to Whitlock's career as a writer, diplomat, and politician. Documents Whitlock's interest in civic progress, municipal administration, improved methods in law enforcement, and conditions in Belgium during World War I, with emphasis on American relief work. Includes Whitlock's journal of a visit by the King and Queen of Belgium to America (1919). Correspondents include Newton Diehl Baker, Nicholas Murray Butler, George Creel, Clarence Darrow, Hamlin Garland, Norman Hapgood, Herbert Hoover, Edward Mandell House, William Dean Howells, Tom Loftin Johnson, Albert Bigelow Paine, Louis F. Post, Lincoln Steffens, and Owen Wister.
Microfilm edition of a portion of the collection available
Microfilm produced by Library of Congress Photoduplication Service from originals in the Manuscript Division.
Author, lawyer, diplomat, and mayor of Toledo.
Collection material in English, with French and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Albert -- I, -- King of the Belgians, -- 1875-1934.; Baker, Newton Diehl, -- 1871-1937 -- Correspondence; Butler, Nicholas Murray, -- 1862-1947 -- Correspondence; Creel, George, -- 1876-1953 -- Correspondence; Darrow, Clarence, -- 1857-1938 -- Correspondence; Elisabeth, -- Queen, consort of Albert I, King of the Belgians, -- 1876-1965.; Garland, Hamlin, -- 1860-1940 -- Correspondence; Hapgood, Norman, -- 1868-1937 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; House, Edward Mandell, -- 1858-1938 -- Correspondence; Howells, William Dean, -- 1837-1920 -- Correspondence; Johnson, Tom Loftin, -- 1854-1911 -- Correspondence; Paine, Albert Bigelow, -- 1861-1937 -- Correspondence; Post, Louis F. -- 1849-1928 -- Correspondence; Steffens, Lincoln, -- 1866-1936 -- Correspondence; Wister, Owen, -- 1860-1938 -- Correspondence; Civic improvement; Law enforcement; Municipal government; World War, 1914-1918 -- Civilian relief; World War, 1914-1918 -- Belgium; Belgium -- Foreign relations -- United States; Ohio -- Politics and government; Toledo (Ohio) -- Politics and government; United States -- Foreign relations -- Belgium; Authors; Diplomats; Lawyers; Mayors -- Ohio -- Toledo